Perbandingan Corak Pemikiran Pendidikan Tasawuf Al-Ghazali dan Sayyed Hossein Nasr - Abas, Ahmad Sirojudin; Gunawan, Agus; Muhajir (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
This research aims to explore and recall the thoughts of Imam Al-Ghazali and Sayyed Hossen Nasr and try to compare their styles of Sufism thought in the field of education. Research using descriptive analysis which aims to systematically and factually describe the facts found, then processed and analyzed according to existing procedures. The conclusion is that Al-Ghazali and Sayyid Hossein Nasr are very influential figures in the world of education, both of them have styles of Sufism thought that are not so different, both of them are able to place Sufism in a balanced way, Al-Ghazali places Shari'a and Sufism in parallel so that both strengthen each other, and so do Sayyed Hossein Nasr. so that both Sufism influenced the way of thinking in the field of education, only Al-Ghazali gained a deep understanding in the field of Sufism after he carried out direct practice after performing a ujlah which ultimately led to immersion in the Sufi world until the end of his life, while Sayyed Hossein Nasr studied Sufism by conducting scientific studies, seeing the gaps that exist in modern humans, who have lost their spiritual spirit.